Stalk cutting mechanism of no-tillage planter for wide/narrow row farming mode - Honglei, Jia; Xinming, Jiang; Hongfang, Yuan; Jian, Zhuang; Jiale, Zhao; Mingzhuo, Guo (International Journal of Agricultural and Biological Engineering, 2017)
A no-tillage planter of narrow row spacing was designed according to the agronomic requirements of wide/narrow row farming mode in the black soil region of Northeast China. Due to the narrow spacing of the seeder unit, a gear-tooth stalk cutting mechanism was designed in order to prevent residues from blocking the planter. The basic parameters, number and edge curve of the stalk cutting blade were designed and optimized. Three-factor and three-level combined orthogonal experiments were conducted using the factors of working speed (1.12 m/s, 1.57 m/s and 2.02 m/s), tillage depth (75 mm, 90 mm and 105 mm) and cutter spacing (15 mm, 30 mm and 45 mm), which significantly affected stalk cutting rate and soil disturbance rate. The optimal combination is the working speed of 1.62 m/s, tillage depth of 92 mm and cutter spacing of 35 mm. Under this condition, the stalk cutting rate is more than 90% and soil disturbance rate is 7.5%-12.0%. The performance of the new no-tillage planter was tested by using the above parameters. The results showed that the no-tillage planter of narrow row spacing came up to the relevant national standards in China. Keywords: conservation tillage, no-tillage planter, wide/narrow row farming, stalk cutting mechanism, soil disturbance rate, direct sowing, corn, Northeast China DOI: 10.3965/j.ijabe.20171002.2247 Citation: Jia H L, Jiang X M, Yuan H F, Zhuang J, Zhao J L, Guo M Z. Stalk cutting mechanism of no-tillage planter for wide/narrow row farming mode. Int J Agric & Biol Eng, 2017; 10(2): 26–35.